CENTRAL AORTIC PRESSURE INDICES IN YOUNG WOMEN WITH EXCESSIVE BODY WEIGHT AND ARTERIAL HYPERTENSION - Bilovol, O.M.; Kniazkova, I.I.; Golovachova, V.O.; Barbashova, V.O.; Kuzminova, N.V.; Sosonna, L.О.; Bogun, M.V. (World of Medicine and Biology, 2025)
This study aimed to investigate changes in central aortic pressure and central hemodynamics, as well as tumor necrosis factor-α and C-reactive protein, in young women with arterial hypertension and excess body weight. The study included 43 young women, aged 18-40 (mean age 36.7±2.3 years), who were referred for an examination due to the detection of elevated blood pressure. Based on office and blood pressure measurements, individuals with persistent stage 1 arterial hypertension were divided into two groups: 20 women with normal body weight (group 1) and 23 women with excess body weight (group 2). The control group consisted of 20 women (mean age 36.5±2.7 years) with normal blood pressure and body weight. Young women with stage 1 arterial hypertension showed significantly greater increases in vascular stiffness and central aortic pressure than the control group. In women with stage 1 arterial hypertension and excess body weight, significantly higher values of central haemodynamic parameters were observed: systolic aortic pressure, diastolic aortic pressure, mean aortic pressure and pulse aortic pressure, as well as pulse wave velocity, compared to a group of patients with arterial hypertension and normal body weight. An increase in serum concentrations of tumor necrosis factor-α and C-reactive protein was observed in female patients with grade 1 hypertension, which was more pronounced in those with excess body weight, which confirms the role of inflammation in the pathogenesis of hypertension in the examined cohort of young women.
Keywords: central aortic pressure; tumor necrosis factor-α; C-reactive protein; arterial hypertension; excess body weight; young women